Can Drinking Microfiltered Raw Immune Milk From Cows Immunized Against SARS-CoV-2 Provide Short-Term Protection Against COVID-19? - Jawhara, Samir (Frontiers in Immunology, 2020)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes severe respiratory tract infections in humans (COVID-19), has become a global health concern. Currently, several vaccine candidates against SARS-CoV-2 are in clinical trials but approval of these vaccines is likely to take a long time before public use. In a previous report, it has been reported the importance of passive immunity and how immunoglobulin (Ig)G collected from recovered coronavirus patients could help in the protection against COVID-19 and boost the immune system of new patients. Passive immunity by immunoglobulin transfer is a concept employed by most mammals and bovine IgG has a role to play in human therapy. IgG is one of the major components of the immunological activity found in cow’s milk and colostrum. Heterologous transfer of passive immunity associated with the consumption of bovine immune-milk by humans has been investigated for decades for its immunological activity against infections. This short review focuses on passive immunity and how microfiltered raw immune-milk or colostrum collected from cows vaccinated against SARS-CoV-2 could provide short-term protection against SARS-CoV-2 infection in humans and could be used as an option until a vaccine becomes commercially available.